The areas of political and social strength of the honorable Saadian state in the countries of the Islamic Maghreb - Bahrami, Azam; Moradi, Hayat (Al-Adab Journal, 2022)
The honorable Saadian state was among the Alawite states in the Islamic Maghreb that was able, by relying on the Ahl al-Bayt (peace be upon him) group and using it as a center of gravity for legitimacy as well as kinship with the Berber tribes, to gain a lot of popularity among the inhabitants of the Maghreb. They managed to form a government in Morocco in the eleventh century after a long period since the fall of Bani Hammoud (5th century AH), the remnants of the Idrisid government in Andalusia. At the time of their rise to power, the Islamic Maghreb was attacked from the outside by European governments, and from within, small, scattered and inconsistent governments clashed.In the meantime, and based on two factors, one belonging to the Ahl al-Bayt (peace be upon them) and the other a jihad to defend the Islamic land against the invading non-Islamic countries, they were able to obtain the necessary acceptance and succeed in forming the government. The current study is based on Parsons' theory of power, and seeks to examine the social and political contexts and the influence of the two on each other in the honorable Saadi government, and is intended to answer the question what are the contexts affecting the formation and progress of this government in the contexts of political and social power in the Islamic Maghreb? It seems that Sharaf al-Saadi, by using channels such as the attribution to the family of the Prophet (PBUH) and Ahl al-Bayt (PBUH), and proximity to the barbarians and the sheikhs of the corners, was able to gain influence through. channels of motivation, influence, as well as ensure and channel power gradually to form and stabilize the foundations of formation their political and social power.